Valor económico de la conservación de la biodiversidad: el caso del Parque Nacional Yanachaga-Chemillén - Lavado-Solis, Karol (2021)
The present study determined the willingness to pay for the conservation of the biodiversity (WTP) of the Yanachaga-Chemillén National Park (YChNP), applying the contingent valuation method, in hypothetical scenarios of conserving 6, 9 or 12 species that guaranteed protection of 50 % of the functionality of the ecosystems of this place. It was found that the WTP was determined by the functional characteristics that key species play in the resilience of the PNYCh ecosystems. For this reason, similar studies should evaluate the option of preferring the use of functionality instead of indicators based, for example, on the number of species.